The impact of size on particle drainage dynamics and antibody response - Simon Zinkhan (14214245) (2021)
Vaccine-induced immune response can be greatly enhanced by mimicking pathogen properties. The size and the repetitive geometric shape of virus-like particles (VLPs) influence their immunogenicity by facilitating drainage to secondary lymphoid organs and enhancing interaction with and activation of B cells and innate humoral immune components. VLPs derived from the plant Bromovirus genus, specifically cowpea chlorotic mottle virus (CCMV), are T = 3 icosahedral particles. (T) is the triangulation number that refers to the number and arrangements of the subunits (pentamers and hexamers) of the VLPs. CCMV-VLPs can be easily expressed in an E. coli host system and package ssRNA during the expression process. Recently, we have engineered CCMV-VLPs by incorporating the universal tetanus toxin (TT) epitope at the N-terminus. The modified CCMVTT-VLPs successfully form icosahedral particles T = 3, with a diameter of ~30 nm analogous to the parental VLPs. Interestingly, incorporating TT epitope at the C-terminus of CCMVTT-VLPs results in the formation of Rod-shaped VLPs, ~1 μm in length and ~ 30 nm in width. In this study, we have investigated the draining kinetics and immunogenicity of both engineered forms (termed as Round-shaped CCMVTT-VLPs and Rod-shaped CCMVTTVLPs) as potential B cell immunogens using different in vitro and in vivo assays. Our results reveal that Roundshaped CCMVTT-VLPs are more efficient in draining to secondary lymphoid organs to charge professional antigen-presenting cells as well as B cells. Furthermore, compared to Rod-shaped CCMVTT-VLPs, Round-shaped CCMVTT-VLPs led to more than 100-fold increased systemic IgG and IgA responses accompanied by prominent formation of splenic germinal centers. Round-shaped CCMVTT-VLPs could also polarize the induced T cell response toward Th1. To our knowledge, this is the first study investigating and comparing the draining kinetics and immunogenicity of one and the same VLP monomer forming nano-sized icosahedra or rods in the micrometer size. Other Information Published in: Journal of Controlled Release License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jconrel.2021.01.012